Can the opening of China railway express reduce urban carbon emissions? a Difference-in-differences analysis in China - Qiu, Zhiping; Liu, Di; Liao, Qiumin (Frontiers in Environmental Science, 2023)
Most of the studies have focused on the operational aspects of CRE and its impact on economic and innovation activities, but neglected its potential impact on carbon emissions. Based on panel data of 284 cities at the prefecture level and above in China from 2003 to 2019, we empirically investigate the impact and mechanism of CRE opening on urban carbon emissions using multi-period DID model and a mediating effect model. Compared with the control group, we find that the opening of CRE significantly reduces urban carbon emissions by 0.78 percentage points under the premise of satisfying parallel trends. This finding holds after placebo testing, PSM-DID estimation, replacing key variables, excluding other policies and disturbances from the opening of high-speed railway, and overcoming endogeneity problems. The results of mechanism tests show that transportation substitution effect, industrial structure upgrading, economic agglomeration and trade opening are important mechanisms to achieve carbon emission reduction by the opening of CRE. Further heterogeneity tests show that the carbon reduction effect of CRE opening is more pronounced in east-central China, larger and non-resource-based cities. This study is the first to evaluate the carbon reduction effect of CRE opening, which provides an important experience for China to achieve the climate goal of "carbon peaking and carbon neutrality".